The Influence of Predictive Analytics, Agile Workforce Leadership, and Robotic HR Interface on Organizational Innovation in West Java Automotive Manufacturers - Immamah, Eka; Haryanto, Anung; Priyana, Yana (Westscience Press, 2025)
This study investigates the influence of Predictive Analytics, Agile Workforce Leadership, and Robotic HR Interface on Organizational Innovation in West Java’s automotive manufacturing sector. Employing a quantitative approach, data were collected from 180 participants using a Likert scale (1–5) and analyzed via Structural Equation Modeling - Partial Least Squares (SEM-PLS) 3. The findings reveal that all three predictors significantly enhance organizational innovation, with Robotic HR Interface having the strongest effect, followed by Agile Workforce Leadership and Predictive Analytics. The model demonstrates substantial explanatory and predictive power (R² = 0.794, Q² = 0.788), highlighting the critical role of integrating technology and agile leadership in fostering innovation. The study contributes to the literature on innovation by emphasizing the interplay of technological tools and leadership strategies in a dynamic industrial context.